বংলাদেশের সামাজিক সমস্যা : স্বরূপ ও সমাধান - শওকতুজ্জামান, সৈয়দ (ঢাকা : বাংলা একাডেমী, 1993)
Study on the social problems in Bangladesh and their remedies.
In Bengali; includes passages in English.
Includes bibliographical references (p. [361]-391).
Keywords: Social problems -- Bangladesh; Bangladesh -- Social conditions; Bangladesh -- Social policy